Increased petrogenic and biospheric organic carbon burial in sub‐Antarctic fjord sediments in response to recent glacier retreat - Berg, Sonja; Jivcov, Sandra; Kusch, Stephanie; Kuhn, Gerhard; White, Duanne; Bohrmann, Gerhard; Melles, Martin; Rethemeyer, Janet; Jivcov, Sandra; 1 Institute of Geology and Mineralogy University of Cologne Cologne Germany; Kusch, Stephanie; 2 CologneAMS—Centre for Accelerator Mass Spectrometry University of Cologne Cologne Germany; Kuhn, Gerhard; 3 Alfred‐Wegener‐Institut Helmholtz Zentrum für Polar‐ und Meeresforschung Bremerhaven Germany; White, Duanne; 4 Centre for Applied Water Science, Institute for Applied Ecology University of Canberra Canberra Australian Capital Territory Australia; et al. (Limnology and Oceanography, 2021)
Fjords are recognized as hotspots of organic carbon (OC) burial in the coastal ocean. In fjords with glaciated catchments, glacier discharge carries large amounts of suspended matter. This sedimentary load includes OC from bedrock and terrigenous sources (modern vegetation, peat, soil deposits), which is either buried in the fjord or remineralized during export, acting as a potential source of CO2 to the atmosphere. In sub‐Antarctic South Georgia, fjord‐terminating glaciers have been retreating during the past decades, likely as a response to changing climate conditions. We determine sources of OC in surface sediments of Cumberland Bay, South Georgia, using lipid biomarkers and the bulk 14C isotopic composition, and quantify OC burial at present and for the time period of documented glacier retreat (between 1958 and 2017). Petrogenic OC is the dominant type of OC in proximity to the present‐day calving fronts (60.4 ± 1.4% to 73.8 ± 2.6%) and decreases to 14.0 ± 2.7% outside the fjord, indicating that petrogenic OC is effectively buried in the fjord. Beside of marine OC, terrigenous OC comprises 2.7 ± 0.5% to 7.9 ± 5.9% and is mostly derived from modern plants and Holocene peat and soil deposits that are eroded along the flanks of the fjord, rather than released by the retreating fjord glaciers. We estimate that the retreat of tidewater glaciers between 1958 and 2017 led to an increase in petrogenic carbon accumulation of 22% in Cumberland West Bay and 6.5% in Cumberland East Bay, suggesting that successive glacier retreat does not only release petrogenic OC into the fjord, but also increases the capacity of OC burial. Deutsche Forschungsgemeinschaft http://dx.doi.org/10.13039/501100001659